Transcriptomic and proteomic analyses of distinct Arabidopsis organs reveal high PSI-NDH complex accumulation in stems - Laihonen, Laura (Wiley-Blackwell, 2025)
In addition to leaves, the main site of photosynthetic reactions, active photosynthesis also takes place in stems, siliques and tree trunks. Although non-foliar photosynthesis has a marked effect on plant growth and yield, only limited information on the expression patterns of photosynthesis-related genes and the structure of photosynthetic machinery in different plant organs has been available. Here, we report the results of transcriptomic analysis of various organs of Arabidopsis thaliana and compare the gene expression profiles of young and mature leaves with a special focus on photosynthetic genes. Further, we analyzed the composition and organization of the photosynthetic electron transfer machinery in leaves, stems and green siliques at the protein level using BN-PAGE. RNA-Seq analysis revealed unique gene expression profiles in different plant organs and showed major differences in the expression of photosynthesis-related genes in young as compared to mature rosettes. Gel-based proteomic analysis of the thylakoid protein complex organization further showed that all studied plant organs contain the necessary components of the photosynthetic electron transfer chain. Intriguingly, stems accumulate high amounts of PSI-NDH complex, which has previously been implicated in cyclic electron transfer.